Enhancing Quality Management Systems (ISO 9001) Implementation in Pakistan’s Manufacturing Industry: A Case Study - Khan, Zohaib; Yusof , Yusri; Yazid Saif; Mohd Rus, Anika Zafiah (Journal of Advanced Mechanical Engineering Applications, 2024)
The ISO 9001 certification is widely recognized for its ability to bolster a company’s commitment to meeting customer needs, thereby ensuring the reliability of high-quality products. ISO 9000 stands out as one of the most successful offshoots of the quality revolution that swept through the 1980s. The quality standards set forth by ISO 9001:2015 are globally renowned, even within the context of Pakistan. Manufacturing industries play a pivotal role in the growth and expansion of Pakistan’s Gross Domestic Product (GDP). Despite their increasing competitiveness and complexity, the implementation of ISO 9001:2015 within Pakistan’s manufacturing sector remains an elusive endeavor. This study aims to identify the underlying factors that hinder the successful adoption of ISO 9001 in Pakistan’s manufacturing industry and, subsequently, formulate effective solutions to address these challenges. As a developing country, Pakistan heavily relies on its manufacturing industry to contribute to the nation’s overall economic development. However, various issues, particularly the implementation of ISO 9001:2015, pose significant obstacles. This investigation delves into the obstacles related to ISO 9001:2015 implementation within Pakistan’s manufacturing sector. A mixed-method approach was employed for data collection, encompassing both quantitative and qualitative methodologies. The insights gathered through this study hold the potential to provide valuable guidance for enhancing the manufacturing industry’s adherence to ISO 9001 standards, ultimately promoting economic growth in Pakistan.